Beitbridge Town Council bill enquiry application - Mugodo, Tinashe (Midlands State University, 2017)
The basis of this project was to develop a Mobile Bill Enquiry Application. The system development was initiated due to the fact that the current manual meter reading could not produce water bill statements in time and also some readings were estimated leading to revenue loss caused by underestimating the charge as well as over estimating which led to overcharging residents. The proposed system is an android application that will be used by Billing Clerks to capture and calculate bills on the go, residents will enquire bills balances using the application also it will allow the council to send notices to the residents and residents can send complaints to the council using the system. Several alternatives could be used for the development of the application such as outsourcing and improvement but the developer used in house development. Feasibility study was carried out so as to see if the project was technically, economically, socially and operationally feasible. As a result of the feasibility study the application development could commence. Information gathering methodologies such as questionnaires, interviews and observations were used in order to come up with user specifications as well as functional and non-functional requirements of the application to be developed. The application was developed using Android Studio, with Java as the back end and SQLite as the database. Testing of the application was done and the application met user requirements. The application was implemented using parallel changeover strategy because it does not interrupt the ongoing processes of the existing system.